Applied Photochemistry When Light Meets Molecules - Bergamini, Giacomo; Silvi, Serena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph features what happens when light meets molecules. This edited volume contains contributions from an international array of contributors, and it is divided into sections representing a selection of carefully focussed and connected photochemistry topics: energy, technology, medicine, environmental sciences, and art. In each section one or more chapters illustrates relevant aspects of each field, such as artificial photosynthesis and solar energy conversion (energy), light emitting devices and photochromic dyes (technology), and photodynamic therapy and solar filters (medicine). Aimed at students of all levels and researchers active in photochemistry. Applied Photochemistry: When Light Meets Molecules provides an exciting journey through some of the most important current and prospective applications of photoactive molecular systems (Prof Alberto Credi, Università di Bologna).
1. Supramolecular Artificial Photosynthesis -- 2. Solar Energy Conversion in Photoelectrochemical Systems -- 3. Organic Light-Emitting Diodes (OLEDs): Working Principles and Device Technology -- 4. Light-Emitting Electrochemical Cells -- 5. Industrial Photochromism -- 6. Application of Visible and Solar Light in Organic Synthesis -- 7. Photochemical Reactions in Sunlit Surface Waters -- 8. Photodynamic Therapy -- 9. Polymer Nanoparticles for Cancer Photodynamic Therapy Combined with Nitric Oxide Photo release and Chemotherapy -- 10. Chemiluminescence in Biomedicine -- 11. Solar Filters: A Strategy of Photo protection -- 12. Luminescent Chemosensors: From Molecules to Nanostructures -- 13. Photochemistry for Cultural Heritage. .
Keywords: Physical chemistry; Renewable energy sources; Medical sciences; Physical Chemistry; Renewable Energy; Health Sciences